Analyze the Temporal and Spatial Distribution of Carbon Capture in Sustainable Development of Work - Fu-Hsuan Chen; Hao-Ren Liu (Energies)
This study aims to analyze the temporal and spatial distribution of carbon capture technologies worldwide, examining the economic, social, and political developments reflected in related academic literature. By conducting a comprehensive analysis of over 40,000 related documents from 2004 to June 2024, as well as selecting 108 relevant articles from SSCI and SCI journals, the study explores the development of carbon capture technologies from different perspectives through keyword searches, trend analysis, and relevance ranking. The study finds that, in terms of temporal trends, significant progress has been made in carbon capture technologies since 2009, and their importance has surpassed that of carbon trading, becoming one of the core technologies in addressing climate change. Spatial trend analysis shows that North American and European countries are more inclined to prioritize “carbon capture” technologies, while Asian countries focus more on “carbon trading”, reflecting regional differences in economic, policy, and technological development. Although carbon capture technologies hold immense potential for sustainable development, they also face numerous challenges, including balancing technological advancements with economic and policy frameworks. This balance is crucial to ensuring that carbon capture technologies can make a positive contribution to sustainable work, climate action, and environmental sustainability, further transforming the essence of sustainable efforts. To fully realize their benefits, it is essential to recognize and address these challenges.